Graphene aerogel supported Fe5(PO4) 4(OH)3·2H2O microspheres as high performance cathode for lithium ion batteries - Han, Sheng; Wang, Jinzuan; Li, Shuang; Wu, Dongqing; Feng, Xinliang (Journal of Materials Chemistry A, 2014)
Three-dimensional (3D) macroporous graphene aerogel-supported Fe 5(PO4)4(OH)3·2H2O (iron(iii) hydroxide phosphate dihydrate) microspheres (GA/IHPDs) have been fabricated by the hydrothermal mineralization of Fe3+ and PO 43- ions in the presence of graphene oxide (GO). The resulting hybrids own interconnected 3D macroporous frameworks with the IHPD particles (2 μm in diameter) encapsulated in flexible graphene sheets. Used as the cathode material in lithium ion batteries (LIBs), the GA/IHPDs hybrids show an excellent reversible specific capacity of 155 mA h g-1 after 300 cycles at a current density of 50 mA g-1 and maintain the specific capacities of 80 and 56 mA h g-1 at the ultrahigh current densities of 2000 and 5000 mA g-1, respectively. To our best knowledge, such an electrochemical performance of GA/IHPDs is superior to the literature reported graphene and other carbon based LiFePO4, or FePO4 hybrids. With a simple fabrication procedure and desirable electrochemical performance, this method offers a highly promising candidate for commercialized cathode materials of LIBs. This journal is © the Partner Organisations 2014.
CRIS-Team Scopus Importer:2023-03-20